A Strain Rate‐Dependent Constitutive Model for Asymmetric Hardening Behavior of TB9 Titanium Alloy. Issue 12 (30th June 2022) - Jin, Xiaochao; Xu, Qipeng; Qiu, Ji; Jin, Tao; Li, Pan; Hou, Cheng; Liu, Le; Fan, Xueling
Abstract : The TB9 titanium alloy is one of the most promising materials for engineering application due to high strength, high toughness, and corrosion resistance. Constitutive modeling is an important issue for investigating the materials properties and mechanical behaviors of TB9 titanium alloys using the numerical simulation method. This article presents a pressure‐dependent elastoplastic asymmetric constitutive model that has a high capability of describing the deformation behavior of TB9 titanium alloy. The strain rate sensitivity model of strength differential coefficient evolution is proposed for an accurate simulation of the asymmetric yielding effect. Furthermore, an idea of yield surface plotted in the deviatoric stress space is presented for the decoupling of coupling effect of hydrostatic pressure and lode angle. The validity of this constitutive model is confirmed by comparing the compression stress–strain responses calculated using the proposed model with the experimental observations on TB9 titanium alloy. Abstract : Herein, a pressure‐dependent elastoplastic asymmetric constitutive model of TB9 titanium alloy is presented. The strain rate sensitivity model of strength differential coefficient evolution is proposed for an accurate simulation of the asymmetric yielding effect. An idea of yield surface plotted in the deviatoric stress space is presented for the decoupling of coupling effect of hydrostatic pressure and lode angle.